2020
DOI: 10.1111/acer.14306
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Alcohol and the Endocannabinoid System

Abstract: Endocannabinoids are lipid mediators that interact with the same cannabinoid receptors that recognize D 9 -tetrahydrocannabinol (THC), the psychoactive constituent of marijuana, to induce similar effects in the brain and periphery. Alcohol and THC are both addictive substances whose acute use elicits rewarding effects that can lead to chronic and compulsive use via engaging similar signaling pathways in the brain. In the liver, both alcohol and endocannabinoids activate lipogenic gene expression leading to fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 184 publications
0
33
0
Order By: Relevance
“…The role of the endocannabinoid (eCB) neurotransmitter system in the regulation of several alcohol-related behaviors is well documented and summarizable with cannabinoid CB 1 receptor antagonists/inverse agonists inhibiting and cannabinoid CB 1 receptor agonists stimulating alcohol drinking, operant alcohol selfadministration, and reinstatement of alcohol seeking in rats and mice. [1][2][3][4] The adverse neuropsychiatric ef-fects of the prototypic cannabinoid CB 1 receptor antagonist/inverse agonist, rimonabant, have regrettably prevented a proper translation to patients affected by alcohol use disorder (AUD) of the large number of remarkably consistent rodent studies reporting its ''antialcohol'' properties.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the endocannabinoid (eCB) neurotransmitter system in the regulation of several alcohol-related behaviors is well documented and summarizable with cannabinoid CB 1 receptor antagonists/inverse agonists inhibiting and cannabinoid CB 1 receptor agonists stimulating alcohol drinking, operant alcohol selfadministration, and reinstatement of alcohol seeking in rats and mice. [1][2][3][4] The adverse neuropsychiatric ef-fects of the prototypic cannabinoid CB 1 receptor antagonist/inverse agonist, rimonabant, have regrettably prevented a proper translation to patients affected by alcohol use disorder (AUD) of the large number of remarkably consistent rodent studies reporting its ''antialcohol'' properties.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 AEA is produced from N-arachidonoyl-phosphatidylethanolamine by N-acyl-phosphatidylethanolamine-specific phospholipase D, and fatty acid amide hydrolase mediates degradation of AEA. 32,33 In the liver, CB 1 R activation contributes to various liver diseases, such as non-alcoholic fatty liver disease, alcoholic steatosis, inflammation, and fibrosis, whereas cannabinoid receptor 2 (CB 2 R) activation ameliorates the progression of liver disease by inhibiting activation of Kupffer cells. 30,[34][35][36][37][38] Interestingly, both receptors are expressed in most hepatic cells including hepatocytes, HSCs, and immune cells.…”
Section: Endocannabinoid Systemmentioning
confidence: 99%
“…In addition, alcohol-mediated activation of CB1 receptor signaling can induce ERRγ-mediated alcoholic fatty liver [9]. These findings indicate that the CB1 receptor plays a critical role in the pathogenesis of alcoholic liver disease (ALD) including alcoholic fatty liver, liver injury, and liver fibrosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…The endocannabinoid system includes two G protein-coupled receptors: cannabinoid receptor type 1 (CB1) and type 2 (CB2) [1]. The CB1 receptor is expressed in the heart, brain, vascular tissue, and liver, while the CB2 receptor is expressed primarily in cells of immune and hematopoietic systems [2]. It was reported that endocannabinoids, anandamide, and 2-arachidonoylglycerol (2-AG) are associated with neuronal, immune, metabolic, vascular, and reproductive functions.…”
Section: Introductionmentioning
confidence: 99%